2013
DOI: 10.1152/ajpregu.00202.2013
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide induces hypersensitivity of rat capsaicin-sensitive lung vagal neurons: role of TRPA1 receptors

Abstract: -The sensitization of capsaicin-sensitive lung vagal (CSLV) afferents by inflammatory mediators is important in the development of airway hypersensitivity. Hydrogen sulfide (H 2 S) is an endogenous mediator inducing hyperalgesia through transient receptor potential ankyrin 1 (TRPA1) receptors located on nociceptors. We conducted this study to determine whether H 2S elevates the sensitivity of rat CSLV afferents. In anesthetized, artificially ventilated rats, the inhalation of aerosolized sodium hydrosulfide (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 52 publications
(103 reference statements)
4
15
0
Order By: Relevance
“…Wilson et al showed that TRPA1 is the downstream target of both mas-related GPCR (Mrgpr) A3 and Mrgprc11, which act as receptors for the pruritogens chloroquine and BAM8-22, respectively [29]. However, no TRPA1 expression was observed regardless of CKD-aP, suggesting that TRPA1 may be down-regulated by intracellular signals of itch such as H 2 S [30]. Uremic toxins stimulate the production of ROS, such as H 2 O 2 , in mitochondria [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Wilson et al showed that TRPA1 is the downstream target of both mas-related GPCR (Mrgpr) A3 and Mrgprc11, which act as receptors for the pruritogens chloroquine and BAM8-22, respectively [29]. However, no TRPA1 expression was observed regardless of CKD-aP, suggesting that TRPA1 may be down-regulated by intracellular signals of itch such as H 2 S [30]. Uremic toxins stimulate the production of ROS, such as H 2 O 2 , in mitochondria [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Wilson et al showed that TRPA1 is the downstream target of both masrelated GPCR (Mrgpr) A3 and Mrgprc11, which act as receptors for the pruritogens chloroquine and BAM8-22, respectively [25]. But no TRPA1 expression was observed regardless of CKD-aP, suggesting that TRPA1 may be downregulated by intracellular signals of itch such as H2S [26]. Uremic toxins stimulate the production of ROS, such as H2O2, in mitochondria [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…No individual excitatory action but potentiation of the capsaicin‐induced response by NaHS was reported in isolated vagal neurons from rat lungs . Even in this model, respiratory effects of sulfide could be abolished by HC030031 (Hsu et al ., ). CGRP release from peptidergic nerves of rat tracheae was reported in response to stimulation with NaHS.…”
Section: Effects Of Sulfur Species Mediated By Trpa1 Channelsmentioning
confidence: 98%